Mendalami Pengelolaan Keuangan Yayasan Lembaga Pendidikan Sebagai Entitas Berorientasi Nonlaba - Alfi Suhariyani; Arisona Ahmad (Politeknik Negeri Jember, 2023)
The main discussion in this study relates to how the financial management of non-profit-oriented entities in educational institution foundations in Jember Regency. Based on these main issues, this study aims to provide an overview and explanation related to the financial management of non-profit-oriented entities in educational institution foundations in the Jember Regency. This study uses a qualitative method with a phenomenological study approach. The research instrument in this study came from an in-depth interview process with two informants from the Al-Amien Islamic education foundation and the Nurul Islam Educational, da'wah, and social foundation. The results of this study indicate that financial planning and implementation are in accordance with stewardship theory, while the evaluation stage is not in accordance with stewardship theory. In terms of financial reporting techniques, the two foundations still use simple reporting techniques on a cash basis, so they have not implemented ISAK 35.